Estudo de viabilidade econômica com concepção de projeto de usina de reciclagem de RCC Classe A para municípios de pequeno porte - Nicolau, Maiara Fuzatti (2018)
The construction industry is the main generator of waste in the economy. The CW can account for up to 70% of total urban solid waste produced (SINDUSCON, 2015), resulting in a concern for the waste of materials extracted from nature, with their illegal disposal and consequent increase in demand for landfill areas. The CONAMA Resolutions and NBR 15.114 (ABNT, 2004c) presented the guidelines for the correct destination of the residues and the development of the CW recycling activity as one of the ways to solve this problem. In addition, Marques Neto (2003) and Córdoba (2010) demonstrated that almost all CW, represented by Class A waste, can be recycled with the production of recycled aggregates. The development of the recycling of CW class A in Brazilian territory was verified in the research of Miranda, Angulo and Carelli (2009) with the identification of 24 units of plants in the State of São Paulo, with only 3 located in small municipalities, with population below 100.000. At the same time, even with lesser generation of waste, they together contribute a significant percentage of CW generation, representing 87.90% of the total municipalities of the State of São Paulo (IBGE, 2010). In this sense, this research had as objective the accomplishment of technical visits based on the content of the bibliographical revision with the proposal of basic project that resulted in the presentation of technical parameters and elaboration of costs for an economic feasibility analysis on the implantation and operation of recycling plants of CW class A, in three case studies defined as small municipalities, with a population range between 10 and 100 thousand inhabitants. The municipality of Severínia with production of 3.70 t / h of recycled aggregates presented the project as not feasible. The municipalities of Monte Alto and Votuporanga, with a production of 6.50 t / h and 13 t / h, respectively, presented as a viable investment with positive net present value and capital recovery.